Study on Strength Attenuation Characteristics of Residual Expansive Soil under Wetting-Drying Cycles and Low Stress and Its Relationship with Shallow Landslide. (14th September 2022) - Chang, Jin; Ma, Jieling; Tang, Xianyuan
Abstract : The rapid development of expansive soil fissures and the attenuation of strength under the action of repeated atmospheric wetting-drying cycles have a very adverse impact on the shallow stability of expansive soil slope. In this study, shear strength test and fissure observation test were performed on typical residual expansive soil specimens at various wetting-drying cycles and low stress. The results show that the shear strength index of residual expansive soil should be obtained according to the high and low stress sections, respectively. The cohesion of the three residual expansive soils decreased to a similar low value range (0~5 kN) at multiple wetting-drying cycles and low stress; the attenuation of cohesion is the main cause of shallow slope collapse. The fissure rate of the specimen surface increases with the increasing number of wetting-drying cycles, and increasing the dry density can significantly inhibit the development of fissures. The repeated wetting-drying cycles leads to the rapid development of slope fissures from the surface to the inside, destroys the internal natural structure of undisturbed expansive soil, reduces the cementation between soil particles, and leads to the decrease of soil cohesion. For slope stability analysis of residual expansive soil, the strength parameters of the specimens with multiple wetting-drying cycles and internal fissure network should be selected according to the overburden pressure of the slope sliding surface. The research results provide a theoretical basis for the stability analysis of shallow landslide of expansive soil slope and slope protection design.